2014
DOI: 10.1038/ncomms4823
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic oscillations of the microRNA miR-96-5p play a neuroprotective role by indirectly regulating glutathione levels

Abstract: Glutathione (GSH) is a key antioxidant that plays an important neuroprotective role in the brain. Decreased GSH levels are associated with neurodegenerative diseases such as Parkinson’s disease and Alzheimer’s disease. Here we show that a diurnal fluctuation of GSH levels is correlated with neuroprotective activity against oxidative stress in dopaminergic cells. In addition, we found that the cysteine transporter excitatory amino acid carrier 1 (EAAC1), which is involved in neuronal GSH synthesis, is negativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 46 publications
0
57
0
Order By: Relevance
“…A total of 16 miRNAs were upregulated (bta‐let‐7c, bta‐miR‐23a, bta‐miR‐34a, bta‐miR‐96, bta‐miR‐98, bta‐miR‐182, bta‐miR‐204, bta‐miR‐211, bta‐miR‐221, bta‐miR‐224, bta‐miR‐301b, bta‐miR‐302d, bta‐miR‐449a, bta‐miR‐450a, bta‐miR‐454 and bta‐miR‐1224) while two miRNAs were downregulated (bta‐miR‐132, and bta‐miR‐210) in high compared to low oxygen tension. The miRNA‐96 regulates glutathione (GSH), which when inhibited causes an increase of GSH levels and increases the cell viability in neuronal mouse cells (Kinoshita et al, ). GSH is a nonenzymatic cellular antioxidant, which removes ROS excess by reducing peroxides and hydroperoxides in inactive products (Matos et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 16 miRNAs were upregulated (bta‐let‐7c, bta‐miR‐23a, bta‐miR‐34a, bta‐miR‐96, bta‐miR‐98, bta‐miR‐182, bta‐miR‐204, bta‐miR‐211, bta‐miR‐221, bta‐miR‐224, bta‐miR‐301b, bta‐miR‐302d, bta‐miR‐449a, bta‐miR‐450a, bta‐miR‐454 and bta‐miR‐1224) while two miRNAs were downregulated (bta‐miR‐132, and bta‐miR‐210) in high compared to low oxygen tension. The miRNA‐96 regulates glutathione (GSH), which when inhibited causes an increase of GSH levels and increases the cell viability in neuronal mouse cells (Kinoshita et al, ). GSH is a nonenzymatic cellular antioxidant, which removes ROS excess by reducing peroxides and hydroperoxides in inactive products (Matos et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…(76) Kinoshita and colleagues (77) showed that miR-96-5p indirectly regulated glutathione (GSH) levels, a key antioxidant responsible for eliminating the damaging, oxidative stress-related reactive oxygen species (ROS). (78) Low levels of miR-96-5p reduced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the role of miR-23a-3p treatment on cerebral ischemia-reperfusion injury, the miR-23a-3p angomir (100 mM) (Kinoshita et al, 2014;Selvamani et al, 2012) was administrated via intracerebroventricular injection and the cerebral infarction volume was evaluated after 1 h of ischemia and 24 h of reperfusion by TTC staining. The results showed that miR-23a-3p angomir significantly reduced cerebral infarction volume, as compared with those in the MCAO group ( Fig.…”
Section: 2mentioning
confidence: 99%